New results on Pb-Au collisions at 40 AGeV from the CERES/NA45 experiment - Filimonov, Kirill; Appelshäuser, Harald; Damjanović, Sanja; Dietel, Thomas; Esumi, ShinIchi; Glässel, Peter; Milošević, Jovan; Petráček, Vojtech; Schmitz, Wolfgang; Seipp, Wolfram; Bielčíková, Jana; Specht, Hans Joachim; et al. (Arxiv, 2001)
In 1999 the CERES/NA45 ran at the CERN SPS with a beam energy of 40 GeV/nucleon. The data set comprises about 8.7 millions Pb-Au events with a trigger selection corresponding to approximately the most central 30% of the geometrical cross section. Results on low-mass electron pair analysis are presented. The upgrade of the experimental setup with the radial drift TPC has allowed to enhance hadron physics capabilities of the experiment. New results on hadron spectra (including Lambda) and flow are presented.
Gesehen am 26.02.2020